Using Information Retrieval Activities to Foster Analytical Thinking Skills in Higher Education in Thailand: A Case Study of Local Wisdom Education - Puchumni, Puchit; Tungpradabkul, Sumalee; Magee, Ratana (Asian Journal of Education and Training, 2019)
Three information retrieving lessons were designed to foster analytical thinking in freshmen with minimal prior active learning experience. Thailand Local Wisdom contents were used as an online information platform due to the scarcity in well-established credible information sources. The lessons were collaborative learning both within own group and between groups. The information retrieving, credibility sorting, classroom sharing, analytical thinking assessments, and self-evaluating activities were conducted in sequential steps and repeated in three trials. A reflective pause was introduced between trials. The self-evaluating pause procedure using teacher’s feedback was possibly a major reason for gains, from 65.0% to 82.5% and to 92.5%, in the number of students exhibiting analytical thinking evidence. A free-response survey after the learning experience showed that the students express high appreciation for the active learning activities as fun and analytical-thinking-promoting learning experiences.